Given that the above is an arithmetic progression , find the common difference.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Relevant wiki: Arithmetic Progressions
Let d denote the common difference.
Since this is an arithmetic progression, the difference between each consecutive terms are equal, namely,
d = ( 4 5 x ) − x = ( 2 9 ) − ( 4 5 x ) .
Simplifying the right side, we have
5 x − 4 x = 1 8 − 5 x
x = 3
d = ( 4 5 x ) − x = 4 5 ( 3 ) − 3
d = 4 3 = 0 . 7 5 .